Uncovering data stream behaviour of automated analytical tasks in edge computing. (19th March 2020) - Hernandez, Lilian; Wachowicz, Monica; Barton, Robert; Breissinger, Marc
Massive volumes of data streams are expected to be generated by the internet of things (IoT). Due to their dispersed and mobile nature, they need to be processed using automated analytical tasks. The research challenge is to uncover whether the data streams, which are being generated by billions of IoT devices, actually conform to a data flow that is required to perform streaming analytics. In this paper, we propose process discovery and conformance checking techniques of process mining in order to expose the flow dependency of IoT data streams between automated analytical tasks running at the edge of a network. Towards this end, we have developed a Petri Net model to ensure the optimal execution of analytical tasks by finding path deviations, bottlenecks, and parallelism. A real-world scenario in smart transit is used to evaluate the full advantage of our proposed model. Uncovering the actual behaviour of data flows from IoT devices to edge nodes has allowed us to detect discrepancies that have a negative impact on the performance of automated analytical tasks.